Gestión de servicio al cliente y sus efectos en el nivel de ventas de la ferretería sermantelec de la ciudad de Riobamba período junio 2016 - junio 2017. - Sotomayor Llerena, Marco Antonio (2018)
The management of customer service is a fundamental part of the company because of it comprises a set of activities designed to find the needs and concerns of the people who come to it. The quality in the service contributes to guarantee to the clients and to promote the goods and/or services offered. The research was aimed at identifying the problems SERMANTELEC in the service it provides to its clients and how this has affected sales. Based on previous research, the study variables were theoretically based on the criteria of different investigators. The inductive method was used because generalities of the behavior of the variables are inferred; the type of research was field and correlational, its design non-experimental; the study population was integrated by the company's clients and the information contained in the invoices from June 2016 to June 2017. The techniques employed were observation and survey. For the application of the surveys, 235 clients were taken as a sample and the data provided by each one of them was analyzed and interpreted, determining that SERMANTELEC has shortcomings in relation to customer service, having to apply corrective measures to ensure customer loyalty, increase the level of sales.